Pembentukan Bank Sampah Sistem Waste Collecting Point (WCP) di Gampong Kayee Lee Kecamatan Ingin Jaya Kabupaten Aceh Besar - Malahayati, Nurul; Nursaniah, Cut; Haris Riyaldi, Muhammad; Nurisra, Nurisra; Suhaeri, Suhaeri; Anoora, Rana; Madris, Madris (Universitas Syiah Kuala, 2024)
The problem of household waste is often found around settlements, such as what happened in Beringin and Lueng Gajah Hamlet, Gampong Kayee Lee, Want Jaya District, Aceh Besar Regency. Household waste piling up on the side of the road, being burned, blocking drainage and causing a foul smell, is a common occurrence. This occurs due to a lack of public awareness and knowledge in managing waste, which results in people not caring about their waste. On the other hand, there is no waste management system managed by the local government. This is proven by the absence of waste facilities and infrastructure provided by the gampong. If this continues, this condition will pollute the environment and cause odor pollution that will damage the environment. Therefore, this Community Service activity aims to maintain the environment of Gampong Kayee Lee so that it is free from waste and becomes an independent village in waste management. Real action is taken by reducing waste generation, as well as increasing the income of partner communities through waste management. Partner 1 is the Beringin Hamlet Community Group (Pokmas) and Partner 2 is the Lueng Gajah Hamlet Pokmas. The activities carried out are building a WCP system Waste Bank and coordinating with DLH, implementing a savings book system for depositing waste that can be cashed in, making handicrafts from inorganic waste for sale. Organic vegetables are also planted and sold in their neighborhood shops. Implementing this system will reduce waste generation and increase income.